Determination of Thermal Lesions Formed by HIFU Using Polyacrylamide Based Phantom Containing Egg White - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2019)
The widespread use of HIFU treatment method in the clinic depends on the effective and safe dosimetric studies. In order to clearly determine the changes occurring in the domain of HIFU, these studies should be performed on materials that mimic the tissue in a transparent structure, rather than the ex-vivo tissues of an opaque structure. In this study, an easy-to-produce, cost-effective, transparent and egg-white polyacrylamide-based phantom is produced which can be observed in synchronized form with HIFU application. HIFU was applied on phantom at different voltage values and different times and the cross-sectional areas and volumes of the lesion regions were calculated in MATLAB program by using image processing methods. In addition, temperature distributions in phantom were determined with the help of T-type ultra-thin thermocouples and the results were compared with each other. © 2019 IEEE.
Keywords: acoustic parameters; cancer; HIFU; image processing: thermocouple.; phantom; temperature increase